Creepy creatures. - Bland, Celia; Resnick, Jane Parker; Resnick, Jane Parker; Matero, Robert (Chicago : Kidsbooks, 1998)
Photographs and text describe bats, snakes, spiders, and lizards.
Bats / by Celia Bland -- Snakes / by Jane P. Resnick -- Spiders / by Jane P. Resnick -- Lizards / by Robert Matero.
Includes index.
5.0
3-6
Keywords: Bats -- Juvenile literature; Snakes -- Juvenile literature; Spiders -- Juvenile literature; Lizards -- Juvenile literature; Bats; Snakes; Spiders; Lizards; Bats; Snakes; Spiders; Lizards